Research advance on cold tolerance in chrysanthemum - Chen, Qingbing; Gao, Kang; Xu, YuRan; Sun, YaHui; Pan, Bo; Chen, Dongliang; Luo, Chang; Cheng, Xi; Liu, Hua; Huang, Conglin (Frontiers in Plant Science, 2023)
Chrysanthemums are one of the top ten most well-known traditional famous flowers in China and one of the top four cut flowers worldwide, holding a significant position in landscape gardening. The cold temperatures of winter restrict the cultivation, introduction, and application of chrysanthemum, resulting in high costs for year-round production. This severely impacts the ornamental and economic value of chrysanthemum. Therefore, research on cold tolerance is of vital importance for guiding chrysanthemum production and application. With the development of genomics, transcriptomics, metabolomics, and other omics approaches, along with high-throughput molecular marker technologies, research on chrysanthemum cold tolerance has been continuously advancing. This article provides a comprehensive overview of the progress in cold tolerance research from various aspects, including chrysanthemum phenotype, physiological mechanisms, positive genetics, molecular mechanisms, and breeding. The aim is to offer insights into the mechanisms of cold tolerance in chrysanthemum and provide reference for in-depth research and the development of new cold tolerance chrysanthemum varieties.